Citra dan Hak Anak Menurut Kakawin Nitisastra - I Nyoman Suarka; A.A. Gede Bawa; Komang Paramartha (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
This article analyses children’s images and rights described in Kakawin Niti??stra, Old Javanese poem about politics and moral didactics). The issue of children’s images and rights have become serious challenges and problems for all components of Indonesian society. Various cases of violence still facing children in Indonesia, including cases of sexual harassment, illegal adoptions, children without birth certificates, drug addicts, to human trafficking. Therefore, fulfillment and protection of the rights of children is a shared responsibility. The issue of children’s images and rights as stipulated in the text Kakawin Niti??stra assess through a critical hermeneutic approach by integrating interpretation and philosophical reflection. Imagery and children’s rights in Kakawin Niti??stra interpreted textual or contextual. Meaning of the text thought out and sought its reflection in relation to the meaning of life. Text Kakawin Niti??stra explain the issue of positive image (suputra) and negative (kuputra). Similarly, the rights of children described in the text Kakawin Niti??stra includes their right to grow and develop, the right to education, the right to receive attention, affection, and protection of various acts of violence